IMPLEMENTASI KURIKULUM 2013 DALAM MATA PELAJARAN BAHASA INDONESIA DI SMA NEGERI 7 PADANG - Marlina, Tesha; Atmazaki, Atmazaki (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACT The purpose of this study is to describe (1) planning of learning Indonesian language in the implementation of 2013 Curriculum in SMA Negeri 7 Padang (2) implementing Indonesian learning in implementing 2013 Curriculum in SMA 7 Padang, and (3) evaluating Indonesian learning in implementing 2013 Curriculum at Padang 7 High School. This type of research is a qualitative research with descriptive methods. This research was carried out in Padang 7 High School. The data in this study are the results of data collection by utilizing guidelines for observation, interviews, and documentation about planning, implementing, and evaluating learning conducted by Indonesian language teachers in SMA Negeri 7 Padang obtained from data sources. The techniques used in the research are observation, interviews, and documentation studies. Techniques used to analyze data are data identification, data presentation, and drawing conclusions.Based on the research findings and research results, the following three things can be concluded. (1) Learning planning in the form of RPP made by Indonesian language teachers in SMA Negeri 7 Padang is mostly in accordance with the principles of RPP preparation contained in Permendikbud Number 22 of 2016 concerning the Process of Primary and Secondary Education. (2) The implementation of Indonesian language learning in SMA Negeri 7 Padang has been carried out with a scientific approach. (3) Assessment in Indonesian language learning at SMA Negeri 7 Padang is carried out with authentic assessment, which includes an assessment of the process and an assessment of results. Teacher 1 and teacher 2 of Indonesian subjects have carried out attitude aspect assessments by observation and journals, knowledge assessment by written tests and assignments and skills assessment by practice / performance, project and product assessments. Kata Kunci: Implementasi, Kurikulum 2013, Mata Pelajaran Bahasa Indonesia